Saúde e Comportamento Sedentário entre Agentes Universitários da Unicentro, Campus Universitário de Irati, PR - Zwaretck, Sheila Regina (2015)
In work environment, the degradation body processes are determined by type of work and how is organized. This ways can transform the work in a pathogenic element, becoming harmful to health (DELCOR et al, 2004). This research relevance is proposing a review in population concept about the relationship to physical activity and healthy behavior. Furthermore understand which the consequences are caused by sedentary diseases and other population customs. The objective this research was identified the physical activities levels according sociodemographic and behavioral factors health related among university agents of UNICENTRO - Irati (PR) Campus. In study were included 58 in a total of 69 university agents. From questionnaires, the participants were submitted to interviews to find the best absorption and precision for the answers. The total of 58 participants, 30 were male sex (51,72%) with average 40,63 years; and, 28 were female sex (48,28%), with average 41,21 years old. In accord to physical activities level, 60% of men and 71,43% for women were classified as not sufficiently active. It was observed that smoking and alcoholic drinks consumption does not interfere on physical activity patterns, because, the population does not have these customs, had high classification as not sufficiently actives too.